2020
DOI: 10.1016/j.jcp.2018.06.027
|View full text |Cite
|
Sign up to set email alerts
|

An entropy stable nodal discontinuous Galerkin method for the resistive MHD equations. Part I: Theory and numerical verification

Abstract: The first paper of this series presents a discretely entropy stable discontinuous Galerkin (DG) method for the resistive magnetohydrodynamics (MHD) equations on three-dimensional curvilinear unstructured hexahedral meshes. Compared to other fluid dynamics systems such as the shallow water equations or the compressible Navier-Stokes equations, the resistive MHD equations need special considerations because of the divergence-free constraint on the magnetic field. For instance, it is well known that for the symme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 57 publications
(94 citation statements)
references
References 53 publications
1
91
0
2
Order By: Relevance
“…With these results, we confirm that the iNS/CH system, (20), with entropy, (37), satisfies the conservation law…”
Section: Property 1 If Inviscid Fluxessupporting
confidence: 75%
“…With these results, we confirm that the iNS/CH system, (20), with entropy, (37), satisfies the conservation law…”
Section: Property 1 If Inviscid Fluxessupporting
confidence: 75%
“…is methodology has been used in the construction of high-order entropy stable DGSEM on quadrilateral/hexahedral elements, e.g. [3,26,60]. In this section, it will be shown that similar ideas can be used to construct high-order entropy stable moving mesh DGSEM, when there are two-point ux functions with the property (2.19) available for the low-order FV method (2.16).…”
Section: Entropy Stable Dgsem On Moving Meshesmentioning
confidence: 99%
“…is methodology has been used in the construction of high-order entropy stable DGSEM on quadrilateral/hexahedral elements, e.g. [3,26,60], or on triangular/tetrahedral elements, e.g. [6,11,14].…”
Section: Introductionmentioning
confidence: 99%
“…The state vector of conserved quantities is u and the Cartesian fluxes are denoted by f 1 , f 2 , f 3 . As in [2,23], we define block vector notation with a double arrow…”
Section: Polytropic Euler Equationsmentioning
confidence: 99%